Electrical Conductivity in Texturally Equilibrated Fluid‐Bearing Forsterite Aggregates at 800°C and 1 GPa: Implications for the High Electrical Conductivity Anomalies in Mantle Wedges. Issue 4 (7th April 2021) - Huang, Yongsheng; Guo, Haihao; Nakatani, Takayuki; Uesugi, Kentaro; Nakamura, Michihiko; Keppler, Hans
Abstract: Aqueous fluids are one of the principal agents of chemical transport in Earth´s interior. The precise determination of fluid fractions is essential to understand bulk physical properties, such as rheology and permeability, and the geophysical state of the mantle. Laboratory‐based electrical conductivity measurements are an effective method for estimating the fluid distribution and fraction in a fluid‐bearing rock. In this study, the electrical conductivity of texturally equilibrated fluid‐bearing forsterite aggregates was measured for the first time with various fluid fractions at a constant salinity of 5.0 wt.% NaCl at 1 GPa and 800°C. We found that the electrical conductivity nonlinearly increases with increasing fluid fraction, and the data can be well reproduced by the modified Archie's law. The three‐dimensional (3‐D) microstructure of the interstitial pores visualized by the high‐resolution synchrotron X‐ray computed micro‐tomography (CT) shows a change in fluid distribution from isolated pockets at a fluid fraction of 0.51 vol.% to interconnected networks at fluid fractions of 2.14 vol.% and above due to grain anisotropy and grain size differences, accounting for the nonlinear increase in electrical conductivity. The rapid increase in conductivity indicates that there is a threshold fluid fraction between 0.51 and 2.14 vol.% for forming interconnected fluid networks, which is consistent with the 3‐D images. Our results provide direct evidence that the presence of >1.0 vol.% aqueous fluid with 5.0 wt.% NaCl is required to explain the high conductivity anomalies above 0.01 S/m detected in deep fore‐arc mantle wedges. Plain Language Summary: Aqueous fluids are one of the principal agents for transporting material in the Earth's interior. Electrical conductivity measurements can be used to reveal the distribution of water in the Earth´s mantle because the presence of a water‐rich fluid in a rock can significantly enhance the bulk conductivity. To better constrain the fluid distribution and fraction in mantle wedges, we measured the electrical conductivity of olivine containing minor amounts of a salt‐bearing aqueous fluid at high pressure and temperature. The three‐dimensional microstructure of the interstitial pores visualized by the high‐resolution synchrotron X‐ray computed micro‐tomography shows that the fluid distribution changes from isolated pockets to interconnected networks with increasing fluid fraction, accounting for the observed nonlinear increase in electrical conductivity. Our results provide direct evidence that the presence of >1.0 vol.% aqueous fluid with 5.0 wt.% NaCl is required to explain the high conductivity anomalies detected in deep fore‐arc regions. Key Points: Electrical conductivity in texturally equilibrated brine‐bearing forsterite aggregates was measured at 800°C and 1 GPa by a novel setup Three‐dimensional images were obtained by synchrotron X‐ray computed tomography to precisely determine the fluid fractions and to visualize the fluid distribution Above 1.0 vol.% fluid with 5 wt.% NaCl is required to explain the high conductivity anomalies above 0.01 S/m in deep fore‐arc mantles